Akibat Hukum Penggeledahan dan Penyitaan Barang Bukti Yang Tidak Sah dalam Pra Peradilan (Studi Kasus Putusan Nomor 1/PID.PRA/2020/PN TLK) - Mahfud Anjali, David; Megawati, Wenny (UNES Law Review, 2024)
The case taken for examination was Decision Number 1/Pid.Pra/2020/PN Tlk, Legal Standing in the decision of the case was the Petitioner because the seizure and search carried out by the Respondent were invalid, because the search and confiscation contained an element of coercive effort which violated limits of the Petitioner's Human Rights, therefore the Petitioner requested the cancellation of the goods/objects confiscated by the Respondent because they were not related to the position of the case. The aim to be achieved in this research is to examine the legal consequences of illegal searches and confiscation of evidence in pre-trial based on Decision Number 1/Pid.Pra/2020/PN Tlk and the judge's considerations based on Decision Number 1/Pid.Pra/2020/PN Tlk. The research method used is normative research, because it examines norms, rules, principles and statutory regulations regarding evidence in Pre-Trial. The results of the research show that the legal consequences that arise are a consequence of illegal seizures and searches, so investigators must return the existing evidence to be returned in accordance with the decision of the Panel of Judges. In Case Number 1/Pid.Pra/2020/PN Tlk the judge in deciding the case had considered three aspects, including those based on juridical, sociological and philosophical aspects. The Panel of Judges granted the Petitioner's favor and ordered the Investigator to return the confiscated items according to legal procedures, and declared that the search carried out by the Respondent of the Petitioner's house was invalid, along with all decisions or determinations issued further regarding the search carried out by the Respondent.